Electron paramagnetic resonance and mass spectrometry: Useful tools to detect ultraviolet light induced skin lesions on a molecular basis – A short review. Issue 1 (2006) - Hochkirch Hochkirch, Ulrike Ulrike; Herrmann Herrmann, Werner Werner; Stößer Stößer, Reinhard Reinhard; Borchert Borchert, Hans-Hubert Hans-Hubert; Linscheid Linscheid, Michael W. Michael W.
Abstract : Ultraviolet radiation is considered responsible for sunburning, premature skin aging, and cancerogenesis through the production of free radical species. Therefore, the favoured possibility for direct detection of unpaired electrons – electron paramagnetic resonance spectroscopy – is predestinated for detection and structural and dynamic analysis of this kind of molecules. However, many of UV induced radicals in skin have a short lifetime at ambient conditions and possibilities for stabilisation or transformation into definite para- or diamagnetic products have to be found. On the other hand, diamagnetic products, potentially also originated by reporter molecules, which are not detectable by EPR, are target molecules for mass spectrometric analysis. In this review, potentials and limitations of both spectroscopic methods are reviewed, and the effect of ultraviolet radiation on human skin is discussed in particular. Suitable combinations of both techniques result in detailed information about photoproducts and processes taking place within skin during and after irradiation. The literature is viewed from a recent perspective; historical aspects were not in the scope of this paper.